Common patterns in the molecular phylogeography of western palearctic birds: a comprehensive review - Pârâu, Liviu G.; Wink, Michael (Journal of ornithology, 2021)
A plethora of studies have offered crucial insights in the phylogeographic status of Western Palearctic bird species. However, an overview integrating all this information and analyzing the combined results is still missing. In this study, we compiled all published peer-reviewed and grey literature available on the phylogeography of Western Palearctic bird species. Our literature review indicates a total number of 198 studies, with the overwhelming majority published as journal articles (n = 186). In total, these literature items offer information on 145 bird species. 85 of these species are characterized by low genetic differentiation, 46 species indicate genetic variation but no geographic structuring i.e. panmixia, while 14 species show geographically distinct lineages and haplotypes. Majority of bird species inhabiting the Western Palearctic display genetic admixture. The glaciation cycles in the past few million years were pivotal factors in shaping this situation: during warm periods many species expanded their distribution range to the north over wide areas of Eurasia; whereas, during ice ages most areas were no longer suitable and species retreated to refugia, where lineages mixed.